PREDISPOSING FACTORS FOR PHYSICAL INACTIVITY IN THE COVID-19 PANDEMIC CONTEXT - Baroni Araujo, Gustavo; Gomes dos Santos, Jordane; Silva Pereira, Paloma; Cesar Pereira da Silva, Júlio; Fernandes de Carvalho Farias, Anderson; da Costa Araújo, Paulo; Guerra Lopes, Laura; Carvalho de Freitas, Maciélia; Pereira Barros, Sabrina; Brito Gonçalves, Vanderleia; Guerra Drummond Júnior, Délio (Journal of Interdisciplinary Debates, 2022)
Introduction: The pandemic caused by the SARS-CoV-2 virus has been causing major impacts on public health. The main risk factor for the development of comorbidities is a sedentary lifestyle, so, due to the readjustment of habits, the emergence of negative impacts from this process is noticeable, such as the increase in physical inactivity and the acquisition of habits harmful to health. In this way, several recommendations have been released drawing attention to the follow-up of physical activity during the pandemic. Objectives: To identify in the literature, scientific evidence about the predisposing factors for physical inactivity during the Covid-19 pandemic. Methodology: This is an integrative literature review, through a descriptive and exploratory effort, carried out in the scientific databases: MEDLINE, SCIELO, BRISA and LILACS. Results and Discussions: From the realization of the titles and abstracts of the articles, 15 studies were selected and after reading in full, 11 were left to compose the final sample. In view of the analysis of the literature, it was evidenced that the lack of adherence to programs for physical exercises at home, through new technologies, blocked the integral assistance to the citizen in the context of the promotion of physical activity, as well as preexisting factors even before the pandemic, such as diseases non-communicable diseases, chronic degenerative diseases, long periods of physical immobility and social inequalities. Final considerations: The study showed that the difficulties in carrying out the practice exist, although there are paths that can be outlined to reverse this scenario. Therefore, public policies to promote physical activity are suggested, which are more consistent on the part of government agencies. In addition, adherence to technological resources also becomes a relevant alternative, combined with health education actions, so that the population has knowledge about the benefits and correct guidelines on how to carry out the practices.